Clusterin secreted by astrocytes enhances neuronal differentiation from human neural precursor cells. - Cordero-Llana, O; Scott, SA; Maslen, S; Anderson, J; Boyle, J; Chowhdury, R; Tyers, P; Barker, R; Kelly, C; Rosser, A; Stephens, E; Chandran, S; et al. (2011)
Neuronal differentiation from expanded human ventral mesencephalic neural precursor cells (NPCs) is very limited. Astrocytes are known to secrete neurotrophic factors, and so in order to enhance neuronal survival from NPCs, we tested the effect of regional astrocyte-conditioned medium (ACM) from the rat cortex, hippocampus and midbrain on this process. Human NPC's were expanded in FGF-2 before differentiation for 1 or 4 weeks in ACM. The results show that ACM from the hippocampus and midbrain increase the number of neurons from expanded human NPCs, an effect that was not observed with cortical ACM. In addition, both hippocampal and midbrain ACM increased the number and length of phosphorylated neurofilaments. MALDI-TOF analysis used to determine differences in media revealed that although all three regional ACMs had cystatin C, α-2 macroglobulin, extracellular matrix glycoprotein and vimentin, only hippocampal and midbrain ACM also contained clusterin, which when immunodepleted from midbrain ACM eliminated the observed effects on neuronal differentiation. Furthermore, clusterin is a highly glycosylated protein that has no effect on cell proliferation but decreases apoptotic nuclei and causes a sustained increase in phosphorylated extracellular signal-regulated kinase, implicating its role in cell survival and differentiation. These findings further reveal differential effects of regional astrocytes on NPC behavior and identify clusterin as an important mediator of NPC-derived neuronal survival and differentiation.